Women, media and crisis : femininity and disorder - Mattelart, Michelle (Comedia publishing group LondonGB, 1986)
This collection of essays discuss the changing role of women in Western and Third World societies. There are three sections. Part one focuses on the image of women projected by the media; part two deals with the feminine ideal and the myth of modernity. The final section discusses the Chilean experience analysing the ideological role of women in the 1973 coup d'etat.